Measurement of phonemic degradation in sensorineural hearing loss using a computational model of the auditory periphery - HINES, ANDREW; HARTE, NAOMI (My University, 2009)
A computational model of the auditory periphery enables faster investigation of new signal processing algorithms for hearing aids. This paper presents a study of the degradation of auditory nerve (AN) responses at a phonetic level for a range of sensorineural hearing losses. The AN model of Zilany & Bruce was used to compute responses to a diverse set of phoneme rich sentences from the TIMIT database. The characteristics of both the average discharge rate and spike timing of the responses are discussed. The experiments demonstrate that the model responses are consistent with respect to impairment and inaudible thresholds.
IET Irish Signals and Systems Conference ISSC 2009
PUBLISHED
Keywords: auditory periphery model, hearing aids, sensorineural hearing loss, phonemic degradation.